2008
DOI: 10.1021/jp8061042
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsions with an Ionic Liquid Surfactant and Room Temperature Ionic Liquids As Polar Pseudo-Phase

Abstract: In this investigation we present for the first time microemulsions comprising an ionic liquid as surfactant and a room-temperature ionic liquid as polar pseudo-phase. Microemulsions containing the long-chain ionic liquid 1-hexadecyl-3-methyl-imidazolium chloride ([C 16 mim][Cl]) as surfactant, decanol as cosurfactant, dodecane as continuous phase and room temperature ionic liquids (ethylammonium nitrate (EAN) and 1-butyl-3methylimidazolium tetrafluoroborate ([bmim]][BF 4 ]), respectively) as polar microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 56 publications
3
119
0
Order By: Relevance
“…At ambient temperature, we chose an experimental path, where the amount of surfactant plus cosurfactant was kept constant at 30 weight percent (P S = 30). 195 By visual observation we noticed that a higher amount of surfactant plus cosurfactant is necessary for a thermal stability up to 150°C at ambient pressure. With increasing amount of surfactant, the thermal stability increased.…”
Section: Sample Handling and Experimental Pathmentioning
confidence: 94%
“…At ambient temperature, we chose an experimental path, where the amount of surfactant plus cosurfactant was kept constant at 30 weight percent (P S = 30). 195 By visual observation we noticed that a higher amount of surfactant plus cosurfactant is necessary for a thermal stability up to 150°C at ambient pressure. With increasing amount of surfactant, the thermal stability increased.…”
Section: Sample Handling and Experimental Pathmentioning
confidence: 94%
“…[41,42]. Numerous studies have explored protein and enzyme stability in these solvents that conclude that the observed catalytic activity of enzymes was due to the heterogeneously dispersed state of enzymes [43][44][45][46]. In our previous work [47], we have categorically shown the efficacy of various imidazolium based ionic liquids in stabilizing protein dispersions.…”
Section: Effect Of Persistence Lengthmentioning
confidence: 93%
“…In this field, Cheng et al (Cheng et al, 2007b) reported the first microemulsion formed by two ILs, i.e., hydrophobic [C 4 mim][PF 6 ] and hydrophilic propylammonium formate (PAF). The formation of IL based microemulsion in supercritical carbon dioxide with N-ethyl perfluorooctylsulfonamide was reported (Zech et al, 2009). Zheng and his coworkers (Li et al, 2009c) reported the phase diagram of p-xylene-[C 14 mim]Br-water ternary system, where hexagonal, lamellar lyotropic liquid crystals or microemulsions formed depending on the composition.…”
Section: Ionic Liquid Based Microemulsionsmentioning
confidence: 99%